A New Method for the Synthesis of 1,4-Diols: C(sp3)–H Hydroxylation Induced by Iron-Catalyzed Redox Hydration of Alkenes - Taniguchi, Tsuyoshi; Hirose, Daisuke; Hashimoto, Takuma (Synlett, 2014)
A novel method for the synthesis of 1,4-diols from alkenes is presented. The reaction is the basis of iron-catalyzed redox hydration of alkenes. The second hydroxyl group is introduced by hydroxylation of an inert C–H bond. The mechanism includes a radical 1,5-hydrogen-transfer process of an intermediary alkoxy radical. In this paper, we describe how this new method has been discovered and developed.
Keywords: alkenes; hydroxylation; iron; oxygen; radicals